Negative relationship between brain-derived neurotrophic factor (BDNF) and attention: A possible elevation in BDNF level among high-altitude migrants - Fan, Jing; Chen, Dongmei; Wang, Niannian; Su, Rui; Li, Hao; Ma, Hailin; Gao, Fei (Frontiers in Neurology, 2023)
Objective Brain-derived neurotrophic factor (BDNF), a member of the neurotrophic family that plays a vital role in regulating neuronal activity and synaptic plasticity in the brain, affects attention. However, studies investigating the association between BDNF and attention in long-term high-altitude (HA) migrants are limited in the literature. As HA affects both BDNF and attention, the relationship between these factors becomes more complex. Therefore, this study aimed to evaluate the relationship between peripheral blood concentrations of BDNF and the three attentional networks in both behavioral and electrical aspects of the brain in long-term HA migrants. Materials and methods Ninety-eight Han adults (mean age: 34.74 ± 3.48 years, 51 females and 47 males, all have lived at Lhasa for 11.30 ± 3.82 years) were recruited in this study. For all participants, the serum BDNF levels were assessed using enzyme-linked immunosorbent assay; event-related potentials (N1, P1, and P3) were recorded during the Attentional Networks Test, which was used as the measure of three attentional networks. Results Executive control scores were negatively correlated with P3 amplitude (r = −0.20, p = 0.044), and serum BDNF levels were positively correlated with executive control scores (r = 0.24, p = 0.019) and negatively correlated with P3 amplitude (r = −0.22, p = 0.027). Through grouping of BDNF levels and three attentional networks, executive control was found to be significantly higher in the high BDNF group than in the low BDNF group (p = 0.010). Different BDNF levels were associated with both orienting scores (χ2 = 6.99, p = 0.030) and executive control scores (χ2 = 9.03, p = 0.011). The higher the BDNF level, the worse was the executive function and the lower was the average P3 amplitude and vice versa. Females were found to have higher alerting scores than males (p = 0.023). Conclusion This study presented the relationship between BDNF and attention under HA. The higher the BDNF level, the worse was the executive control, suggesting that after long-term exposure to HA, hypoxia injury of the brain may occur in individuals with relatively higher BDNF levels, and this higher BDNF level may be the result of self-rehabilitation tackling the adverse effects brought by the HA environment.